The Interaction of Extremist Propaganda and Anger as Predictors of Violent Responses - Shortland, Neil D. (Journal of interpersonal violence, 2021)
In this study, and with a view to extending upon existing findings on the effects of general violent media on violent cognitions, we experimentally measured the relationship between exposure to extremist propaganda and violent cognitions. Our results countered our hypotheses and the wider findings of violent media and aggression that exposure to violent stimuli increases violent thoughts and that this effect is moderated by trait aggression. Specifically, this study found that participants with low and medium trait aggression became more pro-social after being exposed to extremist propaganda. We discuss these results with reference to theories of terror management and mortality salience, as well as the implications of these results for wider theories of the role of online extremist material in the wider “radicalization” process.